The Benefits of Red Betel Leaf Extract for Perineal Wound Healing in BPM Rini District Kediri - Mitayakuna Stianto; Yuly Peristiowati; Siti Farida (Journal for Quality in Public Health, 2018)
Red Betel Leaf contains substances which are effective to treat the wounds. Therefore, it is important to conduct a research to ascertain the difference of healing duration, infection marks, perenium wound pain using red betel leaf 2x/day, red betel leaf extract 1x/day compared with using povidone iodine 10%. This resarch design is in a true experiment with factorial design. The samples are 18 postpartum mother, divided into 3 groups and each is 6 postartum mother, and are chosen with simple random sampling method. The variables that are measured in this research are the healing duration, infection marks, perineum wound pain. This research is also conducted using statistic test one way anova with post hoc as the post test. The result shows that the alpha score is 0.002 which means there is a significant difference of injury care using red betel leaf 2x/day, red betel leaf extract 1x/day with povidone iodine 10% to the duration of healing. The alpha score results at 0.003 shows the significant difference difference of injury care using red betel leaf 2x/day, red betel leaf extract 1x/day with povidone iodine 10% to the infection marks. The alpha score results at 0.021 shows the significant difference difference of injury care using red betel leaf 2x/day, red betel leaf extract 1x/day with povidone iodine 10% to the wound pain. The perineum injury care of postartum mother using red betel leaf extract 2x/day is more efficient and neither does infection marks nor wound pain is found.